Bank Liability Related To Errors In The Implementation Of Customer Fund Transfers (Analysis Of Decision Number 28/PDT.G/2020/PN BTM) - Panca Priyo Hadi Susilo (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study uses a normative juridical legal research method with a case approach in Decision Number 28/Pdt.G/2020/PN Btm and analyzed with an evaluative method. The results of the study show that banks have the responsibility to ensure that every transaction made by customers is carried out correctly. Errors in the execution of fund transfers can cause material losses to customers and damage the bank's reputation. Court decisions regarding banks' liability for fund transfer errors provide important guidance on banks' obligations and the protection of customers' rights.